Down-regulation of lycopene ε-cyclase expression in transgenic sweetpotato plants increases the carotenoid content and tolerance to abiotic stress. (April 2019) - Ke, Qingbo; Kang, Le; Kim, Ho Soo; Xie, Tian; Liu, Chunjuan; Ji, Chang Yoon; Kim, Sun Ha; Park, Woo Sung; Ahn, Mi-Jeong; Wang, Shiwen; Li, Hongbing; Deng, Xiping; et al.
Highlights: We generated transgenic sweetpotato plants (RLE plants) in which expression of IbLCY-ε was down-regulated. RLE plants contained higher levels of total carotenoid and β-carotene. RLE plants were tolerant to MV-mediated oxidative, salt and drought stress. Abstract: Carotenoids are required for many biological processes in plants and humans. Lycopene ε-cyclase (LCY-ε) catalyzes the conversion of lycopene into lutein via the α-branch carotenoid biosynthesis pathway. Down-regulation of IbLCY-ε by RNAi increases carotenoid accumulation and salt stress tolerance in transgenic sweetpotato calli. As the role of IbLCY-ε in carotenoid biosynthesis and environmental stress responses in whole plants is poorly understood, transgenic sweetpotato (RLE plants) with reduced expression of IbLCY-ε were developed. RLE plants contained higher levels of total carotenoid and β-carotene, due to an elevated β-carotene/lutein ratio rather than increased de novo biosynthesis. RLE plants showed high reactive oxygen species/radical-scavenging activity. They also exhibited an enhanced tolerance of both salt and drought stress, which was associated with lower membrane permeability and a higher photosynthetic rate, respectively. Elevated carotenoid accumulation in RLE plants mitigated the reductions in leaf photosystem II efficiency and chlorophyll induced by abiotic stress. Expression of the carotenoid cleavage genes 9-cis-epoxycarotenoid dioxygenase, carotenoid cleavage dioxygenase 1 ( CCD1 ) and CCD4 was higher in RLE plants, as was abscisic acid accumulation. IbLCY-ε silencing thus offers an effective approach for developing sweetpotato plants with increased tolerance to abiotic stress that will grow on global marginal lands with no reduction in nutritional value.